Human Rights Waiver in Criminal Proceedings in Terms of the European Court of Human Rights: ‘Russian Cases’ (Journal of Advanced Research in Social Sciences, 2020)
The article investigates the general position of the European Court of Human Rights on the admissibility and validity of the waiver of rights, the features of the European mechanism for protecting human rights in case of the waiver of the right; studies the case-law practices in criminal cases of the Court in relation to Russia where the Court considered the presence/absence of the waiver of the right. The practice of the ECHR reveals the widespread occurrence of human rights violations in the Russian criminal proceedings with the alleged waiver of the right in the framework of criminal procedure. These includes the situations when the Government claimed that the Applicant had waived his/her right and the Applicant did not agree with this fact and insisted that he had been deprived of the opportunity to exercise his/her right. According to the ECHR, violations of human rights established in the Convention are related not only to shortcomings in the legal system but also to improper law enforcement that does not comply with the Convention requirements. Based on the analysis of the ECHR’s general approaches to the waiver of the right, the authors revealed the compliance of the Russian criminal procedure with the requirements of the Court to the waiver of the right and the guarantees established for it. To achieve the objectives in the HUDOC database of the European Court, using search requests we identified cases against Russia considered by the Chamber and the Grand Chamber, in which the ECHR examined the issue of the presence/absence of the waiver of the right in the criminal procedure. As a result, 40 judgments in which the Court directly considered the issue of the presence/absence of the waiver of the right in the criminal procedure in Russia were selected. We studied and analysed the selected judgments.